SARS-CoV-2-Specific T Cell Responses Are Stronger in Children With Multisystem Inflammatory Syndrome Compared to Children With Uncomplicated SARS-CoV-2 Infection - Conway, Susan R.; Lazarski, Christopher A.; Field, Naomi E.; Jensen-Wachspress, Mariah; Lang, Haili; Kankate, Vaishnavi; Durkee-Shock, Jessica; Kinoshita, Hannah; Suslovic, William; Webber, Kathleen; Smith, Karen; Cohen, Jeffrey I.; et al. (Frontiers in Immunology, 2022)
Background: Despite similar rates of infection, adults and children have markedly different morbidity and mortality related to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Compared to adults, children have infrequent severe manifestations of acute infection but are uniquely at risk for the rare and often severe Multisystem Inflammatory Syndrome in Children (MIS-C) following infection. We hypothesized that these differences in presentation are related to differences in the magnitude and/or antigen specificity of SARS-CoV-2-specific T cell (CST) responses between adults and children. We therefore set out to measure the CST response in convalescent adults versus children with and without MIS-C following SARS-CoV-2 infection. Methods: CSTs were expanded from blood collected from convalescent children and adults post SARS-CoV-2 infection and evaluated by intracellular flow cytometry, surface markers, and cytokine production following stimulation with SARS-CoV-2-specific peptides. Presence of serum/plasma antibody to spike and nucleocapsid was measured using the luciferase immunoprecipitation systems (LIPS) assay. Findings: Twenty-six of 27 MIS-C patients, 7 of 8 non-MIS-C convalescent children, and 13 of 14 adults were seropositive for spike and nucleocapsid antibody. CST responses in MIS-C patients were significantly higher than children with uncomplicated SARS-CoV-2 infection, but weaker than CST responses in convalescent adults. Interpretation: Age-related differences in the magnitude of CST responses suggest differing post-infectious immunity to SARS-CoV-2 in children compared to adults post uncomplicated infection. Children with MIS-C have CST responses that are stronger than children with uncomplicated SARS-CoV-2 infection and weaker than convalescent adults, despite near uniform seropositivity.